Methotrexate-Associated Nonalcoholic Fatty Liver Disease with Transaminitis in Rheumatoid Arthritis - Rajalingham Sakthiswary; Grace Yin Lai Chan; Ee Tzun Koh; Khai Pang Leong; Bernard Yu Hor Thong (The Scientific World Journal)
Background. The aim of this study was to determine the risk factors of MTX-associated nonalcoholic fatty liver disease (NAFLD) with transaminitis in a cohort of rheumatoid arthritis (RA) patients from Singapore. Methods. Patients who developed ultrasound proven NAFLD with transaminitis while on MTX therapy were identified. The demographic and clinical characteristics of the above patients (cases) were compiled and compared with age- and gender-matched controls who were RA patients on long standing MTX therapy without any episode of transaminitis. Results. Among the 978 patients who had received MTX, the prevalence of MTX-associated NAFLD was 4.7% (46 patients). Compared to the controls, the cases had significantly higher mean cumulative dose of MTX (4.03 ± 2.25 g versus 10.04 ± 9.94 g, P≤0.05), weekly dose of MTX (11.3 ± 4.8 mg versus 13.1 ± 4.4 mg weekly, P=0.033), and fasting blood glucose (P=0.029). Following multivariate regression analysis, only cumulative dose of MTX remained significant (P=0.015). Among the cases, the cumulative dose of MTX was found to have a significant positive correlation with the alanine transaminase (ALT) level (P<0.05, standardised beta coefficient 0.512). Conclusion. The cumulative dose of MTX was the only independent predictor of MTX-associated NAFLD with transaminitis.